Lobbying in accounting regulation: analysis of comment letters on the IAS 8 Exposure Draft - Bernado, Giovani Lauretti; Moraes, Romildo de Oliveira (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: Understand how lobbying influenced the comments submitted to the Exposure Draft and comment letters: Accounting Policies and Accounting Estimates—Amendments to IAS 8 – Exposure Draft (IFRS, 2017). Methodology: Categorization of respondents by interest groups, continent of origin, and legal tradition; categorization of responses into six opinion categories; and content analysis of the comments submitted by respondents, organized into semantic structures. Results: The results showed that the lobbying influence was mainly exercised by the groups of “Regulators,” “Representative Bodies,” and “Audit Firms.” Although most respondents were from countries with a Common Law tradition, a convergence of concerns across different legal systems was observed. The influence was primarily manifested through arguments related to the conceptual clarity of the proposed definitions, the need for additional examples to reduce ambiguities, and the preservation of professional judgment freedom. It was also found that the technical quality of the comments had a greater impact on the regulatory process than the mere quantity of responses. Contributions of the Study: The study contributes by demonstrating that lobbying influence in IASB standard-setting amendment processes, as in the case of the Exposure Draft on IAS 8, is not limited to the number of respondents but is strongly shaped by the technical quality and robustness of the arguments presented in the comment letters. The findings reinforce that technical and conceptual factors can override traditional institutional differences—between Common Law and Code Law systems—in international accounting harmonization processes.